Comparison of Nickel and Cobalt Mixed‐Metal Ferrites for Hydrogen Production using Chemical Looping. Issue 10 (8th June 2016) - Aston, Victoria J.; Weimer, Alan W.
Abstract: A simple model of the chemical‐looping hydrogen‐production system was developed to investigate the syngas reduction of and H2 O/O2 oxidation of Fe2 O3, CoFe2 O4, and NiFe2 O4 . The model was used to calculate the metal oxide reduction conversion in a packed‐bed reactor (PBR) before breakthrough of CO/H2, the reduction product gas composition, the steam necessary to fully oxidize the reduced material, and the steam‐associated energy requirements and to analyze the possibility of hybrid H2 O/O2 oxidation for H2 and electricity generation. Model results were compared to laboratory PBR experimental results with additional analysis by thermogravimetric analysis, differential scanning calorimetry, and temperature‐programmed reduction for each material. Use of NiFe2 O4 and CoFe2 O4 was found to increase the flexibility of the chemical‐looping hydrogen process, which allowed more H2 production than is currently possible with Fe‐based materials while maintaining the ability for electricity generation from supplemental O2 oxidation. The mixed‐metal spinel materials were ideally suited for converting lower quality syngas into H2 by lower temperature reactions. Abstract : Flexible fuel : CoFe2 O4 and NiFe2 O4 offer increased flexibility over conventional Fe2 O3 for hydrogen production from chemical looping. Experiments and modeling show these materials have greater H2 recovery, can operate under a wider variety of conditions, and require less volume of material for the same H2 output.